IS SUSTAINABLE RUNNING POSSIBLE? EXPLORING INITIATIVES IN URBAN MARATHONS IN EUROPE - Liwia Delińska (Research on Enterprise in Modern Economy Theory and Practice)
Background and Objective: The increasing popularity of urban marathons has brought significant attention to their impact on sustainability. Despite contributing to numerous economic and social benefits, large-scale events represent a challenge from the perspective of sustainable development. This study aims to identify the communicated sustainability strategies used in organizing marathon running events in Europe and highlight the best practices associated with their implementation.